Population diversity and pathogenicity of Ralstonia solanacearum causing bacterial wilt of tomato in Odisha - Samikshya, Sankalini Pradhan; Subrata, Sarkar; Biswajit, Jena; Anita, Mohanty; Deepali, Mohapatra; Saswati, Sibani Panda; Lipikant, Sahoo; Debashis, Dash (Plant Science Today, 2026)
Bacterial wilt, caused by Ralstonia solanacearum, is one of the most destructive diseases limiting tomato production in tropical and subtropical regions. To understand the pathogen’s biology in Odisha, twenty isolates were collected from wilt-affected tomato fields and characterized for incidence, morphology, biochemical properties, metabolic traits, pathogenic variability and race/biovar grouping. Wilt incidence ranged from 13.33 % to 73.33 %. The most virulent isolates-ORS1, ORS3 and ORS20 (where the ORS series denotes isolates of Ralstonia solanacearum collected from wilt-affected tomato plants across Odisha) caused severe wilt and showed high bacterial populations, whereas isolates such as ORS10 and ORS19 were weakly pathogenic. On tetrazolium chloride (TZC) medium, most isolates formed fluidal, white-margined, red-centred colonies, though variations such as irregular or slimy types were observed. Growth was vigorous on TZC agar, moderate on nutrient agar and poor on King’s B agar. Biochemical and physiological characterization confirmed the identity of all isolates as Ralstonia solanacearum. The isolates exhibited generally conserved metabolic behaviour with limited variability in certain carbohydrate and amino acid utilization patterns, indicating a genetically uniform yet adaptable population across Odisha. All isolates were classified as Biovar III and Race I, infecting tomato, chilli and brinjal but not banana or ginger. These results confirm that tomato wilt in Odisha is dominated by a virulent Biovar III, Race I population with intraspecific variability, underscoring the need for integrated management and resistance breeding against aggressive local isolates.